The decreased competition in expanding versus mature juniper woodlands is counteracted by adverse climatic effects on growth - Gimeno, Teresa E.; Pías, Beatriz; Martínez-Fernández, Jesús; Quiroga, David L.; Escudero, Adrián; Valladares, Fernando (European Journal of Forest Research, 2011)
World-wide deforestation is being reversed in Mediterranean continental areas, where abandonment of traditional practises favours the expansion of valuable habitats, like Juniperus thurifera woodlands. We hypothesised that pre-existing trees facilitate establishment in expanding woodlands, whereas in mature woodlands, competition leads to patch disaggregation. We compared the imprint of these processes on growth, demographic and spatial structure of expanding and mature J. thurifera woodlands. We selected plots where we geopositioned, aged and quantiﬁed the morphological characteristics of all trees. In the mature woodland, trees arranged in clumps and randomly in the expanding woodland. Competition negatively affected growth, was greater in the mature woodland and led to disaggregation of juvenile clumps. Differences in growth between the mature and the expanding woodland disappeared in climatically unfavourable years, suggesting that adverse climate constrains growth more in expanding than in mature woodlands. We suggest that change in the dispersal agents and a decrease of facilitation underlay differences in spatial patters between the expanding and the mature woodland. Observed effective recruitment in less than 30 years into the expanding woodland evidenced that propagule arrival and sapling survival do not constrain woodland expansion. Furthermore, growth of juveniles established in these new areas is favoured by reduced intraspeciﬁc competition. However, we expect growth in expanding woodlands to be negatively impacted by climate change. We conclude that under current global change scenario, conservation of J. thurifera woodlands is favoured by changes in land use, but greater frequency and severity of drier than usual episodes could hamper natural reforestation.
Keywords: Juniperus thurifera; Plant–plant interactions; Radial growth; Spatial pattern; Woodland expansion; Woodlandisation